TINJAUAN SARANA DAN PRASARANA JALUR PEDESTRIAN DI KAWASAN PEUNAYONG, BANDA ACEH - Sri Handayani; Mirza Irwansyah; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Pedestrian path is one of the important elements in urban areas that support mobility of pedestrian movement. Pedestrian accessibility is largely determined by pedestrian track conditions. Pedestrian paths must meet the physical criteria in terms of facilities and infrastructure. The existence of pedestrian path  in Peunayong area which is one of the central business area, trade and service center and heritage area still not equipped with facilities and infrastructure in accordance with the provisions and requirements of the Ministry of Public Works plus the density of activity that occurred in this region caused a change function of the pedestrian itself. The formulation of the problem in this research is how the condition of pedestrian path facilities and infrastructure in Peunayong area is related to the terms, requirements and reviews of the library and accessibility for pedestrians including pedestrians with special needs or have physical limitations. The discussion is based on the results of observations on the condition of pedestrian path  facilities and infrastructure in Peunayong area, comparing it with standard, rules and literature review. Data of observation result will be analyzed by qualitative descriptive method.